Ultrasound May Suppress Tumor Growth, Inhibit Inflammation, and Establish Tolerogenesis by Remodeling Innatome via Pathways of ROS, Immune Checkpoints, Cytokines, and Trained Immunity/Tolerance. (10th February 2021) - Yang, Qian; Zhang, Ruijing; Tang, Peng; Sun, Yu; Johnson, Candice; Saredy, Jason; Wu, Susu; Wang, Jiwei; Lu, Yifan; Saaoud, Fatma; Shao, Ying; Drummer, Charles; et al.
Abstract : Background . The immune mechanisms underlying low-intensity ultrasound- (LIUS-) mediated suppression of inflammation and tumorigenesis remain poorly determined. Methods . We used microarray datasets from the NCBI GEO DataSet repository and conducted comprehensive data-mining analyses, where we examined the gene expression of 1376 innate immune regulators (innatome genes (IGs) in cells treated with LIUS. Results . We made the following findings: (1) LIUS upregulates proinflammatory IGs and downregulates metastasis genes in cancer cells, and LIUS upregulates adaptive immunity pathways but inhibits danger-sensing and inflammation pathways and promote tolerogenic differentiation in bone marrow (BM) cells. (2) LIUS upregulates IGs encoded for proteins localized in the cytoplasm, extracellular space, and others, but downregulates IG proteins localized in nuclear and plasma membranes, and LIUS downregulates phosphatases. (3) LIUS-modulated IGs act partially via several important pathways of reactive oxygen species (ROS), reverse signaling of immune checkpoint receptors B7-H4 and BTNL2, inflammatory cytokines, and static or oscillatory shear stress and heat generation, among which ROS is a dominant mechanism. (4) LIUS upregulates trained immunity enzymes in lymphoma cells and downregulates trained immunity enzymes and presumably establishes trained tolerance in BM cells. (5) LIUS modulates chromatin long-range interactions to differentially regulate IGs expression in cancer cells and noncancer cells. Conclusions . Our analysis suggests novel molecular mechanisms that are utilized by LIUS to induce tumor suppression and inflammation inhibition. Our findings may lead to development of new treatment protocols for cancers and chronic inflammation.